Self-powered semi-passive vibration damping system based on the self-sensing approach. (10th November 2021) - Shen, Hui; Ji, Hongli; Qiu, Jinhao; Yang, Qian; Yu, Mengge; Bian, Yixiang; Ding, Xiaoliang
ABSTRACT: Semi-passive vibration control with the Synchronized Switching Damping on Inductor (SSDI) technique has attracted significant attention in recent years. However, the damping performance of the SSDI technique will be decreased by the lag in detection of switching time. In order to detect switching time without lag, the paper proposes a self-powered semi-passive vibration damping system based on self-sensing approach. In the proposed technique, the switching control signal is obtained by properly processing the voltage of one piezoelectric element which is also used for vibration damping at the same time. Compared with other self-powered SSDI techniques, the proposed approach can detect switching time without lag, while keeping simplicity of implementation with a small number of piezoelectric elements. The proposed technique is also experimentally implemented by a self-powered circuit in the paper. The theoretical analysis, the experimental validation and the drawback of the proposed technique are discussed in the paper.